2019
DOI: 10.1186/s12879-019-4534-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between diabetic and non-diabetic patients with community-acquired pneumonia in primary care in Spain

Abstract: BackgroundDiabetes is one of the underlying risk factors for developing community-acquired pneumonia (CAP). The high prevalence of diabetes among population and the rising incidence of this illness, converts it as an important disease to better control and manage, to prevent its secondary consequences as CAP.The objective of this research is to describe the characteristics of the patients with diabetes and the differences with the no diabetes who have had an episode of CAP in the context of the primary care fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
1
11
0
2
Order By: Relevance
“…This outcome is contrary to that of Wu et al who found no differences between the patients with and without mixed infections in terms of diabetes [ 21 ]. Diabetes is a risk factor for suffering pulmonary infection like community-acquired pneumonia, CAP [ 23 ]. People with diabetes are at two times greater risk of developing a pulmonary infection than healthy people [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is contrary to that of Wu et al who found no differences between the patients with and without mixed infections in terms of diabetes [ 21 ]. Diabetes is a risk factor for suffering pulmonary infection like community-acquired pneumonia, CAP [ 23 ]. People with diabetes are at two times greater risk of developing a pulmonary infection than healthy people [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 15 ] observed a mean age of 60.8 and 59.1 years in diabetics and nondiabetics with pulmonary tuberculosis, respectively. Fernández et al [ 16 ] found a median age of 76.1 and 60.1 years in diabetics and nondiabetics with community-acquired pneumonia, respectively. Park et al [ 17 ] observed a median age of 66.0 and 42.0 years in uncontrolled diabetics and nondiabetics with pulmonary tuberculosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This trend may be explained by greater prevalence of comorbidities in diabetic patients above the age of 60 years. Due to these comorbidities and weakening immune system parallel to increase in age, diabetics become more prone to various infections [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Özellikle, TGP küresel mortalitenin beşinci nedeni olarak sıralanmaktadır. 2 TGP, sorumlu patojenler ve tedaviye konakçı yanıtı açısından oldukça heterojen bir hastalıktır. Komorbiditeler, hastalığın ağırlığının ve buna göre tedavisinin belirlenmesinde önemli bir yer tutmaktadır.…”
Section: Introductionunclassified
“…Fernandez ve ark. 'nın çalışmasında TGP ve diyabetli olguların olmayanlara göre daha yaşlı olduğu ve diyabetli olgularda olmayanlara göre daha fazla pnömoni geliştiği görülmüştür 2. Kardiyovasküler nedenler ve kronik obstrüktif akciğer hastalığı (KOAH) TGP için risk faktörleridir.…”
unclassified